Rethinking State and politics from indigenous autonomy: construction of Autonomous Territorial Government of Wampis Nation - Gómez, Tania (2018)
In the wake of socio-environmental conflict of Bagua (2009)—caused by police violence against indigenous people (awajun and wampis) who defended their collective rights to land—Perú forcibly became the first latin American country to approve a Prior Consultation Law (2011). This seemed to open an institutionalized path for the turbulent and uneven relationship between State and indigenous communities. Despite this, in 2015 Wampis people positioned a divergent political path by publicly declare the articulation of Territorial Autonomous Government of Wampis Nation (GTANW). This article aims to explain the construction of this strategy of territorial defense, from an analysis of the dialectic interaction between political opportunity structure that Bagua conflict opens for the right to self-government; and creative reformulation of wampis political agency that manages to challenge politics inside the State-nations boundaries.